Evaluation of water quality produced by the Mambusao Water District, Mambusao, Capiz - Bayot, Jerilyn Vidal
The quality of the treated water produced by the Mambusao Water Treatment Plant of Mambusao Water District (MWD), Mambusao Capiz was evaluated.